A global fault current limiting strategy for the MMC-HVDC grid with a reduced DC reactor. (September 2022) - Gong, Zheng; Zhao, Sihan; Wu, Xiaojie; Zheng, Changming; Zhou, Juan
Highlights: Design of virtual impedance-based fault current limiting control (VIFCL). Integrated solution for the global fault current limiting at both DC and AC sides of the MMC. Proposing a global fault current limiting control that can reduce the interrupted currents of the DCCB and DC current limiting reactor (CLR). Abstract: The large current limiting reactor (CLR) and DC circuit breaker (DCCB) are required in the half-bridge modular multilevel converter (HB-MMC) project to isolate the DC fault. To limit the fault current and reduce the CLR, a global virtual impedance-based fault current limiting (VIFCL) control strategy is proposed in this paper. This strategy includes two parts: the first part is a simplified adaptive fault current limiting control for limiting the DC fault current by reducing the arm modulating voltage of the MMC adaptively. The second part is a virtual impedance control for limiting the AC currents and the arm currents of the MMCs by mapping the virtual impedance to the reactive power control. The effectiveness of the proposed VIFCL control strategy is verified in the PSCAD/EMTDC using a four-terminal HVDC grid. The proposed global VIFCL control can limit the interrupted currents of the DCCBs and reduce the CLR. The proposed strategy is beneficial for the MMCs to ride through the DC faults safely without a significant influence on the power recovery of the HVDC system.